Homeland – East Prussia, Home – Lithuania: The Case of the Wolf Children - Matimaitytė, Rūta (Genocidas ir rezistencija, 2024)
After Second World War, Soviet Lithuania experienced one of the largest waves of migration from the territory of what was previously East Prussia. By cart, on foot or by freight train, children from East Prussia – alone or with one of their guardians – tried to reach the neighbouring Lithuania. Sick and hungry, these children were forced to find ways to survive in the Soviet-occupied territory, which was plagued with mass deportations, partisan warfare and collectivisation. This is the case of the so-called wolf children who grew up in Soviet Lithuania with the hostile Soviet narrative of their traumatic experience, and tried to convey their traumatic experiences – revealed through the meanings of homeland and home – during trips to Kaliningrad.
Keywords: wolf children; homeland; traumatic experience; East Prussia